2001
DOI: 10.1590/s0100-879x2001000100015
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intraspecific aggression in adult rats by neonatal treatment with a selective serotonin reuptake inhibitor

Abstract: Most studies suggest that serotonin exerts an inhibitory control on the aggression process. According to experimental evidence, this amine also influences growth and development of the nervous tissue including serotoninergic neurons. Thus, the possibility exists that increased serotonin availability in young animals facilitates a long-lasting effect on aggressive responses. The present study aimed to investigate the aggressive behavior of adult rats (90-120 days) treated from the 1st to the 19th postnatal day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
0
37
1
2
Order By: Relevance
“…This is relevant, since enduring effects of early maternal separation may have implications for adult-period vulnerability to the emergence of psychiatric disorders (Andersen et al, 1999). Finally, citalopram administered to neonatal rats reduced aggression in adult animals, suggesting that neuroadaptive mechanisms developed during the neonatal period may last into adult life (Manhaes de Castro et al, 2001).…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…This is relevant, since enduring effects of early maternal separation may have implications for adult-period vulnerability to the emergence of psychiatric disorders (Andersen et al, 1999). Finally, citalopram administered to neonatal rats reduced aggression in adult animals, suggesting that neuroadaptive mechanisms developed during the neonatal period may last into adult life (Manhaes de Castro et al, 2001).…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…The final density and location of the serotoninergic neuron terminals are achieved only during postnatal maturation 18,19 . during pregnancy or the suckling period, pharmacological or nutritional manipulations can induce drastic morphological and functional changes in the growth and development of the nervous system [20][21][22] . Furthermore, the reflex maturation constitutes an indicator of the development of the nervous system 23 .…”
mentioning
confidence: 99%
“…On the other hand, the possibility exists that the effects observed in this experiment may be induced by the action of 5-HT on anorectic mechanisms and not by a direct action of 5-HT on tissues. In fact, it has been well documented that hypophagia induced by citalopram reduces body weight in adult rats (17,34) and body weight gain in young rats (16). Therefore, in the present experiment we could not rule out that the hypophagia induced by citalopram and the resulting malnutrition were capable of causing growth disorders in animals that received citalopram.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, serotonin seems to play a role in regulating the development of the mammalian brain through its action on the production of self serotonin neurons (4,7,8) and on target tis-sues innervated by serotoninergic neurons (9)(10)(11). Pharmacological or nutritional manipulations during pregnancy or the suckling period can induce drastic morphological and functional changes in the growth and development of the nervous system (12)(13)(14)(15)(16). Several studies have shown that treatment with SSRI reduces food intake and body weight in rats (17,18).…”
Section: Introductionmentioning
confidence: 99%